Sources, morphology, phytochemistry, pharmacology of Curcumae Longae Rhizoma, Curcumae Radix, and Curcumae Rhizoma: a review of the literature - Zhu, Xin; Quan, Yun-yun; Yin, Zhu-jun; Li, Min; Wang, Ting; Zheng, Lu-yao; Feng, Shi-qi; Zhao, Jun-ning; Li, Li (Frontiers in Pharmacology, 2023)
Curcumae Longae Rhizoma (turmeric), Curcumae Radix and Curcumae Rhizoma are derived from the Curcuma species, and have gradually become three of the most commonly used medicinal herbs in China due to their different origins, processing methods and medicinal part. These three herbs have certain similarities in morphology, chemical composition, and pharmacological effects.All three of these herbs contain curcuminoids and volatile oil compounds, which exhibit anti-inflammatory, anti-tumor, antioxidant, and neuroprotective properties, although modern clinical applications have their own requirements. At present, there is no systematic guidelines for the clinical application of these three of Curcuma species; consequently, there is a high risk of unwanted phenomena associated with the mixing and indiscriminate use of these herbs. In this review, we focus predominantly on morphology, chemical composition, and the pharmacological activity of these three Curcuma herbs and summarize the current status of research in this field. Our goal is to provide a better understanding of clinical value of these Curcuma species so that we can provide reference guidelines for their further development, utilization and rational clinical application.